Ants in Tropical Urban Habitats: The Myrmecofauna in a Densely Populated Area of Bogor, West Java, Indonesia - AKHMAD RIZALI; MERIJN MARINUS BOS; DAMAYANTI BUCHORI; SEIKI YAMANE; CHRISTIAN HANSJOACHIM SCHULZE (Bogor Agricultural University, Indonesia, 2008)
Ants are the most abundant animals in tropical habitats and have been widely studied in natural and semi-natural tropical systems. However, species in urban tropical habitats remain poorly studied, despite their abundance and potentially important roles in urban ecosystems and pest dynamics. We investigated the ant fauna of Bogor and its surroundings to contribute to the characterization of the myrmecofauna of one of Southeast Asia’s most densely populated regions. Ants were collected both by hand collection and from honey baits in the most common habitats: garbage dumps, households, and home gardens. In total, 94 species were recorded, over two thirds of which occurred in home gardens, which underlines the importance of vegetated habitats for urban planning to support complex ant assemblages. Twelve sampled species are well-known as tramp species that occur primarily in human-dominated landscapes. The two tramp species Anoplolepis gracilipes and Paratrechina longicornis dominated ant assemblages in all locations and most habitat types. The assemblages of tramp species were affected by habitat type, whereas that of non tramp species were not. Forty-five species were also recorded in the Bogor Botanical Garden and five species are also known to be common in cacao agroforests. Hence, research in urban tropical habitats can increase our knowledge of the occurrence of ant species, allowing us to better assess the biodiversity and conservation potential of semi-natural habitats. Key words: ants, tramp species, invasive species, biotic homogenization, urban habitats